2001
DOI: 10.1016/s0887-2333(01)00079-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytamoxifen interaction with human erythrocyte membrane and induction of permeabilization and subsequent hemolysis

Abstract: 4-Hydroxytamoxifen (OHTAM) is the most active metabolite of the widely prescribed anticancer drug tamoxifen (TAM) used in breast cancer therapy. This work describes the effects of OHTAM on isolated human erythrocytes, using standardized test conditions, to check for a putative contribution to the TAM-induced hemolysis and to study basic mechanisms involved in the interaction of OHTAM with cell membranes. Incubation of isolated human erythrocytes with relatively high concentrations of OHTAM results in a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…In addition, it is likely that increased parasitaemia also contributed to higher erythrocyte destruction, which decreased haemoglobin concentration. Another possible explanation is that the metabolism of tamoxifen generated 4-OH-tamoxifen, which by binding to erythrocytes, increased its permeability and promoted lysis, as described by Cruz Silva in humans [47]. Our results show tamoxifen aggravates symptomatology in P. berghei ANKA-infected mice.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, it is likely that increased parasitaemia also contributed to higher erythrocyte destruction, which decreased haemoglobin concentration. Another possible explanation is that the metabolism of tamoxifen generated 4-OH-tamoxifen, which by binding to erythrocytes, increased its permeability and promoted lysis, as described by Cruz Silva in humans [47]. Our results show tamoxifen aggravates symptomatology in P. berghei ANKA-infected mice.…”
Section: Discussionsupporting
confidence: 71%
“…There have been many reports that osmotic fragility (OF) in RBCs is a valuable tool for assessing the actions of various chemicals on the cell membrane in vitro. General [1] and local anesthetics [2], certain kinds of drugs [3] and toxins [4], inorganic [5] and organic compounds [6], as well as substances isolated from plants [7], and crude plant extracts [8], all induce changes in OF in the RBCs of various mammalian species.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that osmotic fragility (OF) in erythrocytes is a useful indicator for evaluating the interactions between various substances and the cell membrane in vitro. It was demonstrated that general [1] and local anesthetics [2], some kinds of drugs [3] and toxins [4], as well as inorganic [5] and organic compounds [6] have the potential to change OF in red blood cells (RBCs). The cholesterol content, which is one of major components of the cell membrane, is known to affect membrane fragility in erythrocytes [7,8].…”
Section: Introductionmentioning
confidence: 99%